2013
DOI: 10.1186/1556-276x-8-224
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ni-silicide/Si heterostructured nanowire arrays by glancing angle deposition and solid state reaction

Abstract: This work develops a method for growing Ni-silicide/Si heterostructured nanowire arrays by glancing angle Ni deposition and solid state reaction on ordered Si nanowire arrays. Samples of ordered Si nanowire arrays were fabricated by nanosphere lithography and metal-induced catalytic etching. Glancing angle Ni deposition deposited Ni only on the top of Si nanowires. When the annealing temperature was 500°C, a Ni3Si2 phase was formed at the apex of the nanowires. The phase of silicide at the Ni-silicide/Si inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the process, as shown in Figure 8 a, SiH 4 molecules arrive on the Ni nanoparticle surfaces and are catalytically decomposed by the catalyst particles which results in forming of a Si layer on the Ni nanoparticles [ 39 ]. Owing to the fast diffusivity of Ni in Si, the formation of NiSi alloys is induced following a solid-state silicide reaction at a substrate temperature above 350 °C [ 40 ]. The spontaneous diffusion of Ni into the deposited Si layer could lead to the elongation of NiSi crystals as well as nanowires as reported in the literature [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the process, as shown in Figure 8 a, SiH 4 molecules arrive on the Ni nanoparticle surfaces and are catalytically decomposed by the catalyst particles which results in forming of a Si layer on the Ni nanoparticles [ 39 ]. Owing to the fast diffusivity of Ni in Si, the formation of NiSi alloys is induced following a solid-state silicide reaction at a substrate temperature above 350 °C [ 40 ]. The spontaneous diffusion of Ni into the deposited Si layer could lead to the elongation of NiSi crystals as well as nanowires as reported in the literature [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…And temperature should be around 500°C during the deposition of the top Si layer so that Ni silicide layer could be intruded into the Si layer to develop the NWs. There are several reports on transition metal silicides which have attracted considerable attention in recent years because of their potential applications in silicon integrated circuits (Kim 2012;Hsu et al 2013;Beregovsky et al 2013;Andrew et al 2010). NiSi and CoSi 2 were emphasized more than other metal silicides due to their low mismatch with the Si lattice, low resistivity, and high thermal stability (Tinani et al 2001;Wu et al 1990).…”
Section: Resultsmentioning
confidence: 99%
“…At the temperatures above 700°C, the agglomeration of the NiSi NWs takes place and NiSi converts into NiSi 2 which shows the undesirable resistivity. Various NiSi NWs growth methods have been reported using chemical (Schmitt et al 2010;Kim 2012), physical , and posttreatment methods (Schmitt et al 2010;Hsu et al 2013). However, little attention has been paid for fundamental investigation regarding the initial stage of silicide formation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the NiSi phase is often accompanied by a Ni-rich phase that forms at lower temperatures [ 215 , 216 , 217 ]. Other crystallographic studies have shown the possibility of obtaining Ni-rich phases such as Ni 31 Si 12 and Ni 2 Si for temperatures between 400 and 450 °C [ 176 , 218 ].…”
Section: Technological Key Elements For Sinw-based Device Integrationmentioning
confidence: 99%